ANALISIS ETIKA BERKOMUNIKASI DALAM INTERAKSI SOSIAL ANTAR PESERTA DIDIK DI SMP NEGERI 18 PONTIANAK - Yuandra, Afrila Muhartisa; Asrori, Muhammad; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
study aims to determine the ethics of communicating in social interactions between students at SMP Negeri 18 Pontianak. The research method used is descriptive with a quantitative approach using the form of survey studies . The overall population in this study amounted to 229 students and the sample taken in this study was class VII AG students totaling 56 students, the sample was taken using random sampling, the data collection technique in this study used indirect communication techniques, namely questionnaires distributed through google form link, data analysis using percentage correction . The results showed that verbal communication ethics in social interaction between students obtained 74% results in the high category, non-verbal communication ethics in social interactions between students obtained 76% results in the high category, Based on the above description in general, communication ethics in social interaction between students has been well and correctly carried out on class VII students of SMP Negeri 18 Pontianak.